010 Moyamoya and AVM: a management dilemma. Issue 3 (9th February 2012) - Redgrave, J; Chadha, D; Patel, U; Randall, M
Abstract : History: A 46 year right handed lady presented with dysphasia and right hemiparesis. Vascular risk factors included smoking and hypertension. Investigations: Angiography revealed moyamoya compromising flow through the left terminal ICA and MCA with evidence of left MCA infarction on CT/MRI. Complicating this was a left frontal AVM fed predominantly from the right carotid through the anterior circle of Willis with an associated flow aneurysm. Treatment Decisions: The patient improved. This raised concern about further hypoperfusion in the moyamoya affected MCA territory. Revascularising this with an EC-IC bypass addresses the hypoperfusion but runs the risk of rupturing the delicate moyamoya vessels. In this case the AVM could also be 'stealing' blood contributing to the clinical scenario. Given that the main supply to the AVM was from the right carotid, we elected to perform the bypass graft urgently with a view to slowly obliterating the AVM afterwards with radiosurgery. Discussion: The patient tolerated the bypass graft without complications and post-operative imaging showed normal perfusion of both cerebral hemispheres. The results of radiosurgery are awaited. This case presented unique management dilemmas because of the complex haemodynamic changes in this unusual combination of pathology.